Proceedings of the 2018 ACM/IEEE International Conference on Human-Robot Interaction 2018
DOI: 10.1145/3171221.3171266
|View full text |Cite
|
Sign up to set email alerts
|

Mindless Robots get Bullied

Abstract: Humans recognise and respond to robots as social agents, to such extent that they occasionally a empt to bully a robot. e current paper investigates whether aggressive behaviour directed towards robots is in uenced by the same social processes that guide human bullying behaviour. More speci cally, it measured the e ects of dehumanisation primes and anthropomorphic qualities of the robot on participants' verbal abuse of a virtual robotic agents. Contrary to previous ndings in human-human interaction, priming pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 61 publications
(108 reference statements)
1
43
0
Order By: Relevance
“…If humans automatically see robots as social beings, including assigning them a moral status, then why do they get aggressive to robots in the wild? It has been suggested that the consequences of the recognition of robots as social agents extend to the field of robot abuse [5,34,54]. Because a robot is perceived as a social agent, aggression towards robots might be predicted by the same factors that drive aggression between humans.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…If humans automatically see robots as social beings, including assigning them a moral status, then why do they get aggressive to robots in the wild? It has been suggested that the consequences of the recognition of robots as social agents extend to the field of robot abuse [5,34,54]. Because a robot is perceived as a social agent, aggression towards robots might be predicted by the same factors that drive aggression between humans.…”
Section: Related Workmentioning
confidence: 99%
“…The current research contributes by combining findings from humanhuman aggression studies with HRI research on the effect of attitudes on negative behaviour. More specifically, by extending previous work on robot abuse [34] we identified and empirically tested four factors that might play a role in robot aggression: the power of the users over the robot, the perceived threat of robots, the robot's embodiment, and the user's attribution of mind towards the robot.…”
Section: Introductionmentioning
confidence: 99%
“…In the physical frame, the unscripted environment opens up possibilities for exploration, and affordances invite action. The literature on human-robot interaction is rife with reports of children and adults engaging with robots in ways that are unexpected by the designers of these systems, such as bullying Keijsers and Bartneck (2018) and abusing Nomura et al. (2016) the robot as well personalizing Sauppé and Mutlu (2015) and attributing preferences Lee et al.…”
Section: Mechanismsmentioning
confidence: 99%
“…To overcome these problems, researchers have resorted to less destructive forms of abuse with more sophisticated robots. For instance, robot bullying has been operationalised as reducing a robot's electrical power supply [4,19] or using abusive language [5]. Using the framework of Game Theory, robots have also been withheld points or money [31].…”
Section: Literaturementioning
confidence: 99%
“…One approach to understanding robot bullying has been to experimentally study what makes people aggressive towards robots [4][5][6]. However, experiments designed so, i.e.…”
Section: Introductionmentioning
confidence: 99%